Impact of Tomato Varieties and Maturity State on Susceptibility of Tomatoes to Salmonella - Massimiliano Marvasi; George Hochmuth; Max Teplitski (EDIS)
Non-typhoidal Salmonella has emerged as one of the problematic human pathogens associated with fresh produce, nuts, and complex foods containing them. Recent research shows that some varieties of plants are more “resistant” to colonization by the pathogens than others. This raises the intriguing possibility that cultivar selection could be used to identify crop varieties that may be less conducive to proliferation of human pathogens. This 3-page fact sheet provides up-to-date information about tomato production practices and their relationships with Salmonella. Written by Massimiliano Marvasi, George Hochmuth, and Max Teplitski, and published by the UF Department of Soil and Water Science, December 2014. (Photo: Max Teplitski, UF/IFAS)